Facilitating the Development and Utilization of a Digital Business Application - Asiati, Diah Isnaini; Syahril, Muhammad; Reza, Muhamad Okto; Putridhinata, Zeva Apriliya; Sahputra, Rendy (Universitas Muhammadiyah Palembang, 2026)
The utilization of the internet has undergone significant transformation, particularly in relation to changes in digitalization-based transaction techniques. These techniques have been rapidly adopted by business actors and effectively utilized to understand and develop markets through the use of business applications. Although business applications are not unfamiliar methods, many business actors still do not fully understand them and are not skilled in utilising them in conducting daily transactions. One such group consists of Micro, Small, and Medium Enterprises (MSEMs/UMKM) that are members of the Nasyiatul 'Aisyiyah Entrepreneurs Association (APUNA) under the coordination of the Nasyiatul 'Aisyiyah Regional Leadership (PD NA) in Palembang City. Therefore, mentoring activities on the use of digital business applications, particularly sales applications, were carried out for APUNA members. The method used in this community service activity involved the delivery of theoretical materials followed by practical mentoring through four stages: (1) a survey to identify business constraints (revealing a strong need for digital marketing training), (2) socialization covering concepts and practices of business digitalization, (3) discussion to ensure shared understanding, and (4) hands-on practice in using sales applications. The results show that this mentoring activity improved APUNA members' skills in using sales applications increasing from 11.8% to 58.8%.